Parasexual genetics of Torulopsis glabrata. - Whelan, W L (1987)
Prototrophic hybrids were generated in the asexual yeast Torulopsis glabrata by the fusion of spheroplasts derived from parent strains which bore complementing auxotrophic markers. The DNA content (per cell) of two hybrids was essentially that predicted by summing the corresponding parental values. UV irradiation of these two hybrids resulted in the formation of sectored colonies with genetic properties consistent with their origin by either mitotic recombination or chromosomal nondisjunction.